A contrivance of 277 nm DUV LD with B0.313Ga0.687N/B0.40Ga0.60N QWs and AlxGa1–xN heterojunction grown on AlN substrate. (December 2019) - Niass, Mussaab I.; Sharif, Muhammad Nawaz; Wang, Yifu; Lu, Zhengqian; Chen, Xue; Qu, Yipu; Du, Zhongqiu; Wang, Fang; Liu, Yuhuai
Abstract: In this paper, an ultraviolet C-band laser diode lasing at 277 nm composed of B0.313 Ga0.687 N/B0.40 Ga0.60 N QW/QB heterostructure on Mg and Si-doped Al x Ga1– x N layers was designed, as well as a lowest reported substitutional accepter and donor concentration up to N A = 5.0 × 10 17 cm –3 and N D = 9.0 × 10 16 cm –3 for deep ultraviolet lasing was achieved. The structure was assumed to be grown over bulk AlN substrate and operate under a continuous wave at room temperature. Although there is an emphasizing of the suitability for using boron nitride wide band gap in the deep ultraviolet region, there is still a shortage of investigation about the ternary BGaN in aluminum-rich AlGaN alloys. Based on the simulation, an average local gain in quantum wells of 1946 cm –1, the maximum emitted power of 2.4 W, the threshold current of 500 mA, a slope efficiency of 1.91 W/A as well as an average DC resistance for the V – I curve of (0.336 Ω) had been observed. Along with an investigation regarding different EBL, designs were included with tapered and inverse tapered structure. Therefore, it had been found a good agreement with the published results for tapered EBL design, with an overweighting for a proposed inverse tapered EBL design.